DEVELOPMENT OF TEST INSTRUMENTS BASED ON SCIENCE LITERATION IN ENERGY MATERIALS IN LIFE SYSTEM - Nurul Elnica; Yennita Yennita; Muhammad Sahal (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2019)
Science literacy is the capacity of individuals to use scientific knowledge to be able to make the right decisions related to nature and human interaction. This study aims to produce test instruments based on scientific literacy on energy matter in living systems. The research method used is Research and Development (R & D) using the ADDIE (Analysis-Design-Development-Implemtation-Evaluation) development model. The stages of the study began with an analysis of the problems of science literacy skills of Indonesian students, then proceeded to develop indicators of questions based on the PISA 2015 indicators. After the indicators were developed, they were followed by making questions and question validation by 3 expert validators. Questions that have been validity tested are limited to 31 students. Data obtained from logical validity and limited trials. Then the data is analyzed descriptively. The results of the analysis of the data obtained are, the validation assessment of science literacy-based test instruments on energy material in living systems by experts is 79.39% with valid validity levels, while the assessment of limited trials is obtained from the validity of 17 questions declared valid and have value reliability of 0.6 with moderate reliability.